2016
DOI: 10.2337/dc15-0764
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospitalization for Heart Failure and Dipeptidyl Peptidase 4 Inhibitors in Patients With Type 2 Diabetes: An Observational Study

Abstract: OBJECTIVETo examine, among patients with type 2 diabetes, the association between hospitalization for heart failure (hHF) and treatment with dipeptidyl peptidase 4 inhibitors (DPP-4is) versus sulfonylureas (SUs), and treatment with saxagliptin versus sitagliptin. RESEARCH DESIGN AND METHODSThis was a retrospective, observational study using a U.S. insurance claims database. Patients initiated treatment between 1 August 2010 and 30 August 2013, and had no use of the comparator treatments in the prior 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 31 publications
3
60
1
Order By: Relevance
“…However, 2 recent observational studies reported no association between heart failure, other cardiovascular outcomes, and treatment with a DPP-4 inhibitor (saxagliptin and sitagliptin), relative to treatment with sulfonylureas [29,30] . A third trial examining alogliptin found no increased risk of cardiovascular mortality among diabetic patients with moderate or severe renal impairment, and a recent observational study of over 1.5 million patients found no increased risk of hospitalization for heart failure when incretin-based drugs were used [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…However, 2 recent observational studies reported no association between heart failure, other cardiovascular outcomes, and treatment with a DPP-4 inhibitor (saxagliptin and sitagliptin), relative to treatment with sulfonylureas [29,30] . A third trial examining alogliptin found no increased risk of cardiovascular mortality among diabetic patients with moderate or severe renal impairment, and a recent observational study of over 1.5 million patients found no increased risk of hospitalization for heart failure when incretin-based drugs were used [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…NDV, normal diet rats treated with vehicle; NDE, normal diet rats treated with enalapril; NDVil, normal diet rats treated with vildagliptin; NDM, normal diet rats treated with metformin; NDC, normal diet rats treated with combined drugs; HFDV, high-fatfed rats treated with vehicle; HFDE, high-fat-fed rats treated with enalapril; HFDVil, high-fat-fed rats treated with vildagliptin; HFDM, high-fat-fed rats treated with metformin; HFDC, high-fat-fed rats treated with combined drugs. cardiovascular events nor the rate of hospitalization for HF (McInnes et al 2015, Wang et al 2015, Fu et al 2016. However, Suh and colleagues reported otherwise, as they showed that sitagliptin and vildagliptin increased the hospitalization rate for HF after 30 days of medication (Suh et al 2015).…”
Section: Figurementioning
confidence: 99%
“…A recent retrospective, observational study, using information from a US insurance claims database, found no association between hospitalization for heart failure and treatment with a DPP-4 inhibitor relative to SU therapy, or treatment with saxagliptin relative to sitagliptin (Fu et al, 2016). At present, therefore, it remains unclear whether the observation of an increase in hospitalization for CHF with saxagliptin (Scirica et al, 2013) was an adverse effect of this specific therapy or a chance finding.…”
Section: Accepted Manuscriptmentioning
confidence: 89%